Evaluation of the genotoxicity of Euterpe oleraceae Mart. (Arecaceae) fruit oil (açaí), in mammalian cells in vivo - Marques, E. S. [UNESP]; Froder, J. G. [UNESP]; Carvalho, J. C.T.; Rosa, P. C.P.; Perazzo, F. F.; Maistro, E. L. [UNESP] (My University, 2016)
E. oleracea is a tropical plant from the Amazon region, with its fruit used for food, and traditionally, as an antioxidant, anti-inflammatory, hypocholesterolemic, for atherosclerotic disease, and has anticancer properties. The oil of the fruit has antidiarrheic, anti-inflammatory and antinociceptive activities, but without genotoxicity evaluation. Therefore, the aim of this study was to evaluate the genotoxic potential of E. oleracea fruit oil (EOO), in rat cells. Male Wistar rats were treated with EOO by gavage at doses of 30, 100 and 300 mg/kg, for 14 days, within a 24 h interval. The DNA damage in the leukocytes, liver, bone marrow and testicular cells, was assessed by the comet assay, and the clastogenic/aneugenic effects in the bone marrow cells, by the micronucleus test. Our phytochemicals characterization of the EOO showed the presence of vanillic, palmitic, γ-linolenic, linoleic, oleic, cinnamic, caffeic, protocatechuic, ferulic, syringic acids, and flavonoids quercetin and kaempferol rutinoside as the main constituents. Both cytogenetic tests performed showed that EOO presented no significant genotoxic effects in the analyzed cells, at the three tested doses. These results indicate that, under our experimental conditions, E. oleracea fruit oil did not reveal genetic toxicity in rat cells.
Keywords: Arecaceae; Açaí oil; Comet assay; Euterpe oleracea; Micronucleus test; Phytochemical of açai